Development, characterization and application of microsatellite markers in population genetics of the horseshoe crab, Tachypleus gigas Muller, of Peninsular Malaysia - Liew, Pui Ling (2012)
A total of 136 microsatellite sequences were isolated from Tachypleus gigas by using the 5’ anchored PCR technique and 52 primer pairs were designed to flank these repeat regions. Of these, 18 primer pairs were found to be polymorphic and were used to examine the levels of genetic variation for 130 individuals of T. gigas from five populations (Port Dickson, Pantai Bersih, Sungai Muar, Pantai Balok and Kampung Sungai Pulai) collected along the coastal areas of Peninsular Malaysia. The 18 loci generated 51 alleles and the number of alleles per locus ranged from 2 to 6 (average 2.8 alleles per locus) with the mean observed heterozygosities ranging from 0.2590 to 0.3637. All the five populations showed heterozygote deficiencies. Inbreeding, small population size and the presence of null alleles may have contributed to the occurrence of heterozygote deficiency. Cluster analysis revealed that the east coast population (Pantai Balok) was outgrouped from the west coast populations (Port Dickson, Pantai Bersih, Sungai Muar and Kampung Sungai Pulai). This result was in contrast to the Inter Simple Sequence Repeat (ISSR) cluster analysis where the populations were not differentiated in accordance with their geographical distributions by using five ISSR primers which generated 56 polymorphic loci. The possible reasons for were the low number of polymorphic loci used and the limitations of the ISSR technique such as dominant inheritance. In addition, the genetic differences between the polluted population, Port Dickson and the other populations suggested the possible use of T. gigas as a pollution bioindicator based on ISSR markers. The present results obtained from both the microsatellite and ISSR methods provide guidance for their future efficient use in the genetic analysis of horseshoe crabs. The microsatellite markers developed in this study will be useful for investigating the genetic diversity and population structure of T. gigas in the Southeast Asian region.